Development of professional identity in the physical therapist assistant - Leighton, Randall E. (Kansas State University, 2020)
Appropriate professional identity (PI) is a critical component in the make-up of a health care worker. Many different forces influence how the individual sees themselves as a professional including experience, upbringing, education and interactions with individuals in the chosen field. This mixed-methods research used an explanatory sequential research design to explore the forces which help create professional identity through education and into professional work. In the quantitative portion of the study, four groups composed of a) physical therapist assistant students (SPTAs) in their first year of school, b) SPTAs in their second year of school, c) novice physical therapist assistants (PTAs) with three or less years of practice and d) experienced PTAs with more than three years of practice were surveyed. The SPTAs completed the modified professional identity five-factor scale (mPIFFS) (Tan et al., 2017), a 26-question survey utilizing a five-point Likert scale to measure aspects of PI and overall strength of PI. PTAs completed the modified professional identity and values scale (mPIVS) (Eason et al., 2018; Healey & Hays, 2012), a 20-question survey utilizing a six-point Likert scale which explored aspects of PI in the practicing PTA. In the intermediate phase, the two surveys were analyzed for strength of PI and themes amongst the items to inform semi-structured interview questions for the qualitative portion. The qualitative portion consisted of three interviews of individuals in each of the four study groups for a total of 12 interviews. The data from these interviews was used in conjunction with survey results to draw conclusions. Forces affecting PI for the student and practicing PTA were largely the same, including experience, the PTA/PT relationship, role models, and behavioral observation. The most notable difference between the two groups was breadth of experience. This data suggests the implementation of early clinical experience, intentional mentoring, and formalized education in PI.
Keywords: professional identity; physical therapist assistant; student physical therapist assistant